Integration of a palliative approach into heart failure care: a European Society of Cardiology Heart Failure Association position paper. (4th October 2020) - Hill, Loreena; Prager Geller, Tal; Baruah, Resham; Beattie, James M.; Boyne, Josiane; de Stoutz, Noemi; Di Stolfo, Giuseppe; Lambrinou, Ekaterini; Skibelund, Anne K.; Uchmanowicz, Izabella; Rutten, Frans H.; Čelutkienė, Jelena; et al.
Abstract : The Heart Failure Association of the European Society of Cardiology has published a previous position paper and various guidelines over the past decade recognizing the value of palliative care for those affected by this burdensome condition. Integrating palliative care into evidence‐based heart failure management remains challenging for many professionals, as it includes the identification of palliative care needs, symptom control, adjustment of drug and device therapy, advance care planning, family and informal caregiver support, and trying to ensure a 'good death'. This new position paper aims to provide day‐to‐day practical clinical guidance on these topics, supporting the coordinated provision of palliation strategies as goals of care fluctuate along the heart failure disease trajectory. The specific components of palliative care for symptom alleviation, spiritual and psychosocial support, and the appropriate modification of guideline‐directed treatment protocols, including drug deprescription and device deactivation, are described for the chronic, crisis and terminal phases of heart failure. Abstract : Integrating palliative care throughout the heart failure trajectory